Thermal illusion with twinborn-like heat signatures. (December 2018) - Zhou, Shuling; Hu, Run; Luo, Xiaobing
Highlights: General formulas are developed to achieve twinborn-like heat signatures. Experiments and simulations agree well on the thermal bilocation effect. Parametric study is presented for further performance optimization. Abstract: Thermal illusion device, which can change an arbitrary object into another one when observed from an infrared vision, recently has attracted considerable attention amongst a series of innovative thermal phenomena by resorting to the unique thermal metamaterial. To enhance the illusion deceptiveness, current thermal illusion devices mostly change the location or shape of the target, but seldom deal with the number of heat signatures. In this paper, we develop a general formula to enhance the illusion deceptiveness by splitting the thermal target to appear like thermal bilocation with twinborn distinct heat signatures. The exhaustive design process based on transformation thermodynamics is rigorously introduced in order to realize thermal bilocation. Simulative and experimental results agree well with each other and validate the conception of thermal bilocation. Additionally, the influence of three structure parameters on the bilocation effects has been considered for further optimization. Our device can thermally camouflage the original target with twinborn signatures at different locations, improving the deceptiveness greatly compared with only moving or reshaping. The present thermal bilocation not only can fortify the performance of thermal camouflage, but also can stimulate the extension of illusion thermodynamics to further physical applications.